2023
DOI: 10.1177/1934578x231176916
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanism of Schizandrin A in the Treatment of Liver Cancer Using Network Pharmacology, Molecular Docking, and Target Validation

Abstract: Background Liver cancer is a common threat to human health. Schizandrin A (SA) has certain therapeutic effect on liver cancer, but its related mechanism of action is not clear. Elucidating this mechanism is of great significance for the development of drugs to target liver cancer. Objective The objective is to study the effect and mechanism of SA on liver cancer. Methods The potential targets of SA in the treatment of liver cancer were screened based on network pharmacology, and the core targets were further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 12 Our previous study found that Schisandrisin A significantly reduced the inflammation level of HepG2 cells; improved the oxidative stress state; downregulated transforming growth factor beta 1 (TGF-β1), vascular endothlial growth factor (VEGF), phosphoinositide 3-kinase (PI3K), and Akt mRNA levels; inhibited the expression of the PI3K-Akt signaling pathway, and had a significant anti-tumor effect on tumor cells with high activity and small molecular weight, which was an ideal candidate for the production of contrast-enhanced ultrasound microbubbles. 13 Therefore, in this study, Schisandin A was loaded into Span-PEG microbubbles to make ultrasound contrast agent and to play an anti-tumor effect on the lesions of liver cancer, which was rarely reported. This study would provide a new reference for the treatment of liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Our previous study found that Schisandrisin A significantly reduced the inflammation level of HepG2 cells; improved the oxidative stress state; downregulated transforming growth factor beta 1 (TGF-β1), vascular endothlial growth factor (VEGF), phosphoinositide 3-kinase (PI3K), and Akt mRNA levels; inhibited the expression of the PI3K-Akt signaling pathway, and had a significant anti-tumor effect on tumor cells with high activity and small molecular weight, which was an ideal candidate for the production of contrast-enhanced ultrasound microbubbles. 13 Therefore, in this study, Schisandin A was loaded into Span-PEG microbubbles to make ultrasound contrast agent and to play an anti-tumor effect on the lesions of liver cancer, which was rarely reported. This study would provide a new reference for the treatment of liver cancer.…”
Section: Introductionmentioning
confidence: 99%